2012
DOI: 10.1590/s1678-77572012000500003
|View full text |Cite
|
Sign up to set email alerts
|

Impact of filler size and distribution on roughness and wear of composite resin after simulated toothbrushing

Abstract: ObjectivesNanofilled composite resins are claimed to provide superior mechanical properties compared with microhybrid resins. Thus, the aim of this study was to compare nanofilled with microhybrid composite resins. The null hypothesis was that the size and the distribution of fillers do not influence the mechanical properties of surface roughness and wear after simulated toothbrushing test. Material and methodsTen rectangular specimens (15 mm x 5 mm x 4 mm) of Filtek Z250 (FZ2), Admira (A), TPH3 (T),Esthet-X (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
61
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 19 publications
(57 reference statements)
4
61
1
3
Order By: Relevance
“…Studies have shown that the type of glass, shape, and size of filler components, resin matrix formulation, and degree of polymerization have a significant effect on the wear characteristics of resin composite materials. [41][42] It is interesting to note the similarity of Z and SU on the argon-etched SEM examinations ( Figure 5B,G). The manufacturing process appears to result in similarly shaped filler particles, which are mostly rounded.…”
Section: Discussionmentioning
confidence: 97%
“…Studies have shown that the type of glass, shape, and size of filler components, resin matrix formulation, and degree of polymerization have a significant effect on the wear characteristics of resin composite materials. [41][42] It is interesting to note the similarity of Z and SU on the argon-etched SEM examinations ( Figure 5B,G). The manufacturing process appears to result in similarly shaped filler particles, which are mostly rounded.…”
Section: Discussionmentioning
confidence: 97%
“…In fact, Filtek Z350XT showed a smoother surface than Filtek Z250 when specimens were subjected to none of the finishing/polishing treatment (control 1 group), which was also found previously. 13 This result can be explained by the smaller volume and less homogenous …”
Section: Discussionmentioning
confidence: 99%
“…The literature suggests that filler size has the potential to influence the surface characteristics of composite [30][31][32]. This may suggest that nano-filler incorporation response to finishing timing were similar since the ability to produce a smooth surface with the use of the aluminum oxide disks depends on their cutting filler particles and matrix resin equally [33,34]. Since the nanoparticle filler-reinforced dental composites used in this study were highly filled hybrid composites with relatively large filler particles, further investigation focusing specifically in high content nanofiller is a need.…”
Section: Discussionmentioning
confidence: 99%